Comparison of Knowledge Level of 2018 FK UKRIDA Students and Mutiara Bangsa 2 Students about Feminine Wash and Vaginal Discharge - Adrian Goenawan; Johnny Johnny; Aurellia Aurellia (Jurnal MedScientiae, 2022)
The results of the Indonesian Demographic and Health Survey (SKDI) in 2012, showed a prevalence rate of 18% of women aged 15-49 years had experienced vaginal discharge. Many women in society use feminine wash to clean their feminine area. In fact, the use of feminine wash can cause reproductive health problems, which is vaginal discharge. Compare the level of knowledge about feminine wash and vaginal discharge among students of FK UKRIDA batch 2018 and SMA Muiara Bangsa 2 students. This study is an analytical study with a cross-sectional approach. The samples of this study were FK UKRIDA students batch 2018 and SMA Mutiara Bangsa 2 students totaling 145 people with the total sampling method. Research data obtained by using a questionnaire instrument. The results of descriptive statistical analysis showed that from 90 people of FK UKRIDA students’ batch 2018, 51 people (35.2%) had a good level of knowledge, while from 45 SMA Mutiara Bangsa 2 students, only 8 people (5.5%). The results of the Kruskal Wallis test obtained a p-value of 0.000 (<0.05). The level of knowledge of FK UKRIDA students batch 2018 was better than SMA Mutiara Bangsa 2 students about feminine wash and vaginal discharge.